Nilai Estetika Tatak Moccak pada Masyarakat Pakpak Dairi - Ester Natalia Simanjuntak; Martozet Martozet; Sitti Rahmah (Gesture: Jurnal Seni Tari, 2026)
Tatak Moccak, the traditional dance of the Pakpak tribe in North Sumatra, combines dance and martial arts inspired by tiger movements. This research aims to explore the aesthetic values contained in the movements, musical accompaniment, traditional costumes, and the welcoming procession. With a descriptive qualitative approach, data were obtained through observation, interviews, and documentation from sources as well as Tatak Moccak dancers in Hutarakyat Village. The research results show that the aesthetic value of Tatak Moccak is manifested in the harmony of dance movements such as persentabien, bunga-bunga, mundur mi podi, toyong, and santah, which have symbolic meanings. Additionally, the accompaniment of traditional music creates beauty through rhythms and melodies that harmonize with the dance movements, while traditional attire, such as oles eket takal and baju merapi-api, adds visual appeal. Tatak Moccak also plays an important role in traditional ceremonies and welcoming rituals as a symbol of the cultural identity of the Pakpak tribe. However, the lack of recognition among the younger generation poses a challenge in preserving this dance. Therefore, educational and cultural promotion efforts are key to ensuring the sustainability of Tatak Moccak in the future.